RESPONSE OF DIFFERENT CUCUMBER HYBRIDS TO GRAFTING ON SQUASH ROOTSTOCK - Abdul Razzaq, A. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was conducted at Unifert Research Station Yousfiah Center of Iraq during spring of 2015 by grafting five cucumber hybrids named Mayadine, Ghazeer, Najim, Emparator and Beit Alpha on the rootstock ES101 (Cucurbita maxima x Cucurbita moschata) used the hole Insertion technique. The experiment content 10 treatments which were the grafted and ungrafted hybrids using randomized complete block design with three replications. The results showed that grafted Emparator (C4G) gave asignificans increase in the number of leaves (124.20 leaf.plant-1), leaf area (1.85 m2), chlorophyll leaf content (603.0 mg.100 g-1), plant dry weight (191.7 g.plant-1) and the amount of absorbed (nitrogen, phosphorus and potassium) by square area which were (17.77, 1.11 and 14.82 g.m-2, respectively). However, grafted Nagim (C3G) showed an increase in fruit count (14.03 fruit.plant-1), plant yield (1.53 kg.plant-1, early yield (10.60 ton.ha-1) and total yield (28.77 ton.ha-1).